Influence of OH Scavenger on the Water Effect on Secondary Organic Aerosol Formation from Ozonolysis of Limonene, Δ3-Carene, and α-Pinene - Jonsson, Åsa M; Hallquist, Mattias; Ljungström, Evert (Environmental science & technology, 2008)
The effect of OH scavengers on how water vapor influences the formation of secondary organic aerosol (SOA) in ozonolysis of limonene, Δ3-carene, and α-pinene at low concentrations has been investigated by using a laminar flow reactor. Cyclohexane and 2-butanol (3−40 × 1013 molecules cm−3) were used as scavengers and compared to experiments without any scavenger. The reactions were conducted at 298 K and at relative humidities between <10 and 80%. The yield of SOA decreased in the order “no scavenger” > 2-butanol > cyclohexane. The effect of water vapor was similar for 2-butanol and without a scavenger, with an increase in particle number and mass concentration with increasing relative humidity. The water effect for cyclohexane was more complex, depending on the terpene, scavenger concentration, and SOA concentration. The water effect seems to be influenced by the HO2/RO2 ratio. The results are discussed in relation to the currently suggested mechanism for alkene ozonolysis and to atmospheric importance. The results imply that the ozone-initiated oxidation of terpenes needs revision in order to fully account for the role of water in the chemical mechanism.